Gamma Knife Stereotactic Radiosurgery for Brain Metastases Using Only 3 Pins. Issue 6 (20th October 2016) - Ho, Jennifer C.; Luo, Dershan; Guha-Thakurta, Nandita; Ferguson, Sherise D.; Ghia, Amol J.; Yang, James N.; Brown, Paul D.; Voong, Khinh Ranh
Abstract: BACKGROUND: Removal of a pin during Gamma Knife stereotactic radiosurgery (GK-SRS) may be necessary to prevent collision and allow treatment. OBJECTIVE: To investigate outcomes after GK-SRS for treatment of brain metastases using a head frame immobilized to the skull with only 3 pins. METHODS: Between 2009 and 2014, we retrospectively reviewed the records of 1971 patients and identified 20 patients with multiple brain metastases treated with GK-SRS in which 1 anterior pin was removed immediately before treatment of a single posterior lesion. GK-SRS was also delivered to 116 other lesions in these 20 patients using the standard 4 pins during the same session, serving as an internal control for comparison. Endpoints included local control, dosimetric parameters, toxicity, and overall survival. RESULTS: The median number of lesions treated per session was 6 (range, 2-14). The lesions treated using 3 pins were located in the occipital lobe (n = 14) or the cerebellum (n = 6). Median follow-up was 12.3 months. There was 1 local failure involving a control lesion. Lesions treated using 3 pins had a lower prescription isodose line. GK-SRS of a lesion using 3 pins did not cause any clinical toxicities or increase in radiographic edema or hemorrhage. CONCLUSION: Treating posteriorly located brain metastases with GK-SRS using only 3 pins provided excellent local control and no difference in treatment toxicity, which may make it a safe and reasonable option for lesions that may otherwise be difficult to treat.